Effect of Comparison Ration on Performance of Combined Cycle Gas Turbine - Thamir K., Ibrahim; M. M., Rahman (Scientific & Academic Publishing, 2012)
It is known the performance of a gas turbine (GT) has strong dependence of climate conditions. A suitable solution to minimize this negative effect is to raise inlet turbine temperature and reduce temperature of inlet air to GT com-pressor. Combined cycles gas turbines (CCGT) are a lot used to acquire a high-efficiency power plant. Increases the peak compression ratio has been proposed to improve the combined-cycle gas-turbine performance. The code of the performance model for CCGT power plant was developed utilizing the MATLAB software. The simulating results show that the overall efficiency increases with the increase of the peak compression ratio. The total power output increases with the increase of the peak compression ratio. The peak overall efficiency occurs at the higher compression ratio with low ambient tempera-ture and higher turbine inlet temperature. The overall thermal efficiencies for CCGT are higher compared to gas-turbine plants.